2016
DOI: 10.15324/kjcls.2016.48.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Population Density of Rodents and Chigger Mites in Gokseong-gun of Jeollanam-do, Korea

Abstract: in the Gokseong-gun of Jeollanam-do, Korea. A total of 79 rodents were collected using Sherman collapsible traps, and among them, 73 were Apodemus agrarius (92.4%), 4 were Crocidura lasiura (5.0%), and 2 were Microtus fortis (2.5%). Sixty-eight out of the 79 rodents were parasitized by chiggers, showing an infestation rate of 86.0% and a chigger index of 74.5; the chigger index of A. agrarius was 75.4. From the trapped field rodents, 5,063 chigger mites were collected and identified with 6 species of 2 genera.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
5
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 9 publications
4
8
5
2
Order By: Relevance
“…; Lee et al . ; Song ), which is similar to the parasitization rate of 91% from the present study. In particular, the herein obtained parasitization rate of C. lasiura was 29%, but it has been reported to be 18% (Song et al .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…; Lee et al . ; Song ), which is similar to the parasitization rate of 91% from the present study. In particular, the herein obtained parasitization rate of C. lasiura was 29%, but it has been reported to be 18% (Song et al .…”
Section: Discussionsupporting
confidence: 91%
“…), which indicates that the TR of 9.8 in our study was slightly low. The infection rate for wild rodents in our study was 72%, which is lower than the 86% value reported by Song (), but higher than the 69% and 50% values reported by Song et al . () and Lee et al .…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations